Ameliorative effect of gallic acid on doxorubicin-induced cardiac dysfunction in rats (2017)
Background: The use of doxorubicin (DOX) as an antineoplastic agent has been greatly limited because of the myriad of toxic sequelae associated with it. The aim of this study was to assess the protective effects of gallic acid (GA) on DOX-induced cardiac toxicity in rats. Methods: Sixty male rats (Wistar strain) were used in this study. They were divided into six groups (A–F) each containing 10 animals. Group A was the control. Rats in Groups B, C, and D were treated with DOX at the dosage of 15 mg/kg body weight i.p. Prior to this treatment, rats in Groups C and D had been treated orally with GA for 7 days at the dosage of 60 and 120 mg/kg, respectively. Animals from Groups E and F received only 60 and 120 mg/kg GA, respectively, which were administered orally for 7 days. Results: The exposure of rats to DOX led to a significant (p 0.05) decrease in the cardiac antioxidant defence system and elevation of creatine kinase myocardial band and lactate dehydrogenase. The electrocardiography results showed a significant decrease in heart rate, QRS, and QT-segment prolongation. GA alone improved the antioxidant defence system. Conclusions: The GA pretreatment significantly alleviated GA-associated ECG abnormalities, restored the antioxidant status and prevented cardiac damage.